POTENSI TANDAN KOSONG SAWIT UNTUK MEMPRODUKSI KOMPOS - Munawir Munawir (Sekolah Tinggi Manajemen IMMI, 2018)
Indonesia to the implementation of additional plantation development program and in particular on the development of oil palm , area and production of CPO (Crude Palm Oil) is increasing.Indonesia to 2014 year (preliminary figures) there are 10.956.231 ha, 29.344.479 tons of CPO, derived from 127.355.037 tons of FFB (Fresh Fruit Branch), potentially acquired 29.291.657 tons EFB (Empty Fruit Branch) and 18.307.284 tons EFB compost. Benefits than to produce EFB compost can be for pulp, fibreboard and fuel. EFB compost nutrient content and beneficial advantages both for fertilizer crops and prove soil structure. EFBis necessary to use the maximum potential for composting EFB and for the benefits.